Portal Dobreknjige.si - Malec, Luana (Organizacija znanja, 2025)
Dobreknjige.si is an online platform designed for readers seeking high-quality fiction and non-fiction recommendations. As a national project of Slovenian public libraries, it helps users organize their reading and connect with fellow readers, and promotes a vibrant reading culture. The portal attracts over two million visits annually, with its popularity steadily increasing. After a decade of operation, a major upgrade became necessary due to outdated technology, limited development possibilities and the need to meet modern user expectations. The revamped portal introduces advanced search features, including the Four Doors concept, Literary GPS and cover colour filtering, making book discovery more intuitive. Interactivity has been significantly enhanced, offering features such as reading journals, quizzes and a curated collection of literary quotes. Improved personalization allows users to follow books, authors, and genres. Additionally, the new platform prioritizes accessibility for users with special needs and fosters greater community involvement in content creation. With these updates, Dobreknjige.si remains Slovenia’s leading book recommendation portal, nurturing a dynamic reading culture and strengthening connections within the literary and library communities.
Keywords: bralna priporočila; Dobreknjige.si; online portals; reading recommendations; Slovenian public libraries; slovenske splošne knjižnice; spletni portali